The Burden of Hepatitis B Among People Living with HIV in East Africa: Evidence from 2016?2019 Population-Based HIV Impact Assessment Surveys - Genamo, Mitiku Tamre (Department of Public Health and Family Medicine, 2025)
Background: Hepatitis B Virus (HBV) co-infection remains a critical public health challenge among people living with HIV (PLWH), particularly in sub-Saharan Africa (SSA). Africa, which is second to Asia in chronic HBV prevalence, globally it was reported approximately 60 million cases in 2017, with nearly 74% of global HBV/HIV co-infections occurring in the SSA region. In East Africa, hepatitis B surface antigen (HBsAg) prevalence rates are as follows: Ethiopia (6.03%), Uganda (9.19%), Kenya (5.16%), Rwanda (6.67%), and Tanzania (7.17%). In countries like Kenya, the infection rates surpass 5%, and Africa accounts for 70% of all new cases of HBV infections globally. Despite extensive research on the HIV epidemic, data on HBV co-infections among PLWH remain limited. Objectives: This study aimed to estimate the prevalence of HBV co-infection among PLWH in East Africa and identify related sociodemographic and clinical factors. Methods: Part A of this Minor dissertation details the research protocol, covering the rationale for the study in the introduction, objectives, methodology, statistical analysis plan, and ethical considerations. Part B provides a comprehensive literature review of studies conducted in sub-Saharan Africa (SSA), exploring the available research on the burden of Hepatitis B and its risk factors among people living with HIV (PLWH). Part C presents the study findings in a journal-formatted manuscript, including results, discussions, limitations, and recommendations. Part D covers the materials used in Parts A, B, and C as appendices, followed by the PLOS ONE journal's instructions to authors. Finally, Part E is the policy brief to inform decision-making. The entire thesis follows the Vancouver referencing style, in line with the requirements of the selected journal for manuscript formatting. A cross-sectional analysis of secondary data from the PHIA surveys conducted in Ethiopia, Kenya, Rwanda, Tanzania, and Uganda from 2016 to 2019 by Colombia university. Data for secondary analysis was extracted from the PHIA dataset between April 2024 – August 2024. The study ii employed stratified multistage probability sampling to select households and participants aged 15– 64 years living with HIV. Data collection, conducted via mobile tablets, covered demographic, clinical, and HIV-related variables. HBV status was assessed through rapid diagnostic tests. Ethical approval was obtained for both primary data collection and secondary analysis per the Helsinki Declaration guidelines. Statistical analysis was performed in R, including descriptive measures, logistic regression, and significance testing (P < 0.05). Results: A total of 4,944 PLWH were included in this analysis, of the total 4,944 PLWH screened for HBV 248 (5.02%) were HBV-positive. The median age of PLWH participants was 36.5 years (IQR: 30– 45), while HBV-negative participants had a median age of 38 years (IQR: 30–47). Males accounted for 42% of HBV-positive cases, compared to 29% among HBV-negative individuals. The overall HBV prevalence among PLWH was 5.02% (95% [CI]: 4.42% – 5.66%), with different country-specific prevalence: Rwanda 3.49% (95% CI: 2.40% – 4.89%), Tanzania 4.29% (95% CI: 0.89% – 12.02%), Kenya (4.99%), Ethiopia 5.54% (95% CI: 3.86% – 7.65%), and Uganda 5.67% (95% CI: 4.65% – 6.84%). Females had higher odds of HBV infection than males (aOR 1.78, P=0.003). Additionally, those who are HBV positive exhibited higher HIV viral loads (≥1,000 copies/mL; 39% vs. 31%) and lower median CD4 counts (455 vs. 488.5 cells/μL). Participants with viral suppression had 1.4 times higher odds of HBV infection than those without viral suppression (OR = 1.40; 95% CI: 1.08–1.82; P = 0.01). Active syphilis infections were more common among HBV-positive individuals (5%) than HBV-negative participants (3%). Conclusion: HBV co-infection remains a significant concern among PLWH in East Africa, with notable country-level variations. It remains a burden that poses an additional challenge to the national health system, which is already battling various infectious and non-infectious diseases. The findings underscore the importance of enhanced HBV screening, vaccination, and integrated treatment approaches to reduce the dual burden of HIV and HBV.